(untitled) (TAJ: Journal of Teachers Association, 2023)
Objective: The present study is to ascertain the relative frequency, histologic types, and age distribution of both neoplastic and non–neoplastic ovarian lesions in the Rajshahi medical college hospitals and compare the results with similar studies in other regions of this country and abroad. Methods & Materials: This cross-sectional study was conducted in the Department of Pathology, Rajshahi Medical College, over one year from January 2021 to December 2021. A total of 144 cases of ovarian lesions were included in this study. Inflammatory conditions and developmental anomalies were excluded. Result: Out of 144 cases of ovarian masses studied, 104 (72%) were neoplastic. The common types were Surface epithelial tumors (70%), germ cell tumors (23%), and sex-cord stromal tumors (7%). The age range of ovarian tumors was 5 to 70 yrs, and the highest incidence was between 21-50 yrs. Most of the ovarian tumors were bilateral (85%). Conclusion: Varying types of both non-neoplastic and neoplastic ovarian lesions were seen. Benign tumors were more common than malignant tumors in all age groups. Surface epithelial cell tumors, followed by germ cell tumors, were the most common tumor. Serous cystadenoma was the most common tumor. Tumour types varied in different age groups. TAJ 2022; 36: No-1: 17-22